Physical and mental decline and yet rather happy? A study of Danes aged 45 and older - Vestergaard, Sonja (Aging Ment Health, 2014)
OBJECTIVES: Little is known about whether the feeling of happiness follows the age-related decline in physical and mental functioning. The objective of this study was to analyze differences with age in physical and mental functions and in the feeling of happiness among Danes aged 45 years and older. METHOD: Three Danish population-based surveys including 11,307 participants aged 45+ years, of whom 2411 were in the age group of 90+, were conducted in the period 1995–2001. The participation rate in the three surveys was between 63% and 82% and the same design and the same instrument were used. Self-reported mobility, a cognitive composite score, and a depression symptomatology score including a question about happiness were assessed. T-score metric was used to compare across domains and age groups. RESULTS: Overall, successively older age groups performed worse than the youngest age group (45–49 years), and the estimated linear decline was greater after age 70 than before age 70. For example, when comparing the oldest age group (90+ years) with the youngest, the T-score differences were found to be the largest for the mobility score (men: 40.2, women: 41.4), followed by the cognitive function (men: 22.0, women: 24.9), and the total depression symptomatology score (men: 15.5, women: 17.4). Conversely, the T-score difference in happiness was small (men: 5.6, women: 6.0). CONCLUSION: Despite markedly poorer physical and mental functions with increasing age, in this Danish sample age did not seem to affect happiness to a similarly notable extent, although, in this study, cohort and age effects cannot be disentangled.